2022
DOI: 10.4236/jmmce.2022.104023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Clay Materials from Ivory Coast for Their Use as Adsorbents for Wastewater Treatment

Abstract: In order to contribute to the valorisation of the clay materials of Ivory Coast in the depollution of wastewater, the physicochemical and mineralogical characterization of three clay samples taken in Agboville (AGB), Bingerville (BIN) and Katiola (KAT) was carried out. The objective of this work was to compare the properties of the clays in order to identify the one that is likely to have interesting adsorptive capacities to clean up contaminated water. These clays were studied by chemical analysis, X-ray diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The results of chemical analysis by ICP-OES are recorded in elements) and Table 3 (minor elements). The clays studied are characterized by: • A comparable loss on ignition for samples K1, K2 and K3, but it is lower for sample K7, which confirms its siliceous nature in agreement with a previous study carried out in Tunisia [11]; • Contents of silica SiO 2 , alumina Al 2 O 3 and iron oxide Fe 2 O 3 for all samples (K1 to K7) similar to Katiola clay [12].…”
Section: Icp-oes Analysissupporting
confidence: 88%
“…The results of chemical analysis by ICP-OES are recorded in elements) and Table 3 (minor elements). The clays studied are characterized by: • A comparable loss on ignition for samples K1, K2 and K3, but it is lower for sample K7, which confirms its siliceous nature in agreement with a previous study carried out in Tunisia [11]; • Contents of silica SiO 2 , alumina Al 2 O 3 and iron oxide Fe 2 O 3 for all samples (K1 to K7) similar to Katiola clay [12].…”
Section: Icp-oes Analysissupporting
confidence: 88%
“…The mineralogical composition of the two clays gives the KAT sample (SBET = 48.5 m 2 /g and CEC = 35.5 meq/100g) greater adsorbent properties than BIN (31.7 m 2 /g and CEC = 6. 2 meq/100g) [11]. The mineralogical and physicochemical characteristics of these two clays explain their difference with respect to the elimination of metals.…”
Section: Trace Metal Element Content After Treatment With Claysmentioning
confidence: 95%
“…Due to their sheet structure and their interesting adsorbent properties linked to their large specific surface area and their cation exchange capacities, clays are used in the depollution of contaminated solutions as adsorbents [9,10]. In addition, several studies have shown that Côte d'Ivoire has numerous clay sites with interesting adsorbent properties [11]. Following the above, the objective of this work is to depollute water from a gold panning site using two clays from Ivory Coast.…”
Section: Introductionmentioning
confidence: 99%
“…This is why the recovery of this waste constitutes a real opportunity for the development of this sector. Among other things, some water purification methods such as filtration, coagulation, flocculation sedimentation have been used and reported [7] [8] [9]. To contribute to minimizing the risks associated with the poor management of waste from mangoes in the prefecture of Mamou, research work is directed towards the recovery of wet waste from mangoes into bio-gas by methanation, and the cores could be used for the production of adsorbent for the purification of polluted water and drying of mangoes in order to minimize the throwing of mango waste in the open air, in the production sites [10] [11].…”
Section: Introductionmentioning
confidence: 99%